ALAT PEMBERSIH KARAT OTOMATIS MENGGUNAKAN SENSOR pH SEBAGAI PENGUKUR TINGKAT KEASAMAN CAIRAN BERBASIS IoT - Nirwana, Rengga; Paramitha, Nina; Purwanto, Timur Dali; Dasmen, Rahmat Novrianda (Rang Teknik Journal, 2025)
The chemical and process industries require precise control systems to manage critical parameters, such as the pH level in solutions, especially in the treatment of acidic liquid waste. One of the main challenges in this industry is the effective neutralization of acidic waste to prevent damage to the environment and infrastructure. IoT-based pH sensors offer an innovative solution by enabling real-time, remote monitoring and control of pH levels. With IoT integration, pH sensor data can be accessed directly, improving operational efficiency and decision-making accuracy. Furthermore, automatic pH regulation based on collected data minimizes human error and enhances safety. In testing, the ultrasonic and TDS sensors integrated with relay and motor pump modules demonstrated 100% accuracy in controlling devices based on distance and TDS values. The entire system operated with a very low error percentage, confirming its reliability for application in the chemical industry.Keywords: Internet of Things (IoT), pH sensor, pH control, liquid waste, ultrasonic sensor, TDS sensor, automation, chemical industry